The outcomes of carbapenem resistant enterobacteriaceae (CRE) infected patients and their association with antibiotic therapy - Musa, Norazizah (2018)
Introduction Carbapenem Resistant Enterobacteriaceae (CRE) especially Carbapenem producing CRE (CP-CRE) has emerged as a global threat which commonly associated with hospital acquired infection including blood stream infection, pneumonia, surgical site infection and urinary tract infection. Overall, isolation of CRE from any site whether this represents clinical infection or not was associated with poor outcomes. Despite their increasing burden, the most optimal treatment for CRE infections was largely unknown. Therefore, the aim of this study is to determine the outcomes of CRE infected patients and their association with antibiotic therapy. Methods This was a retrospective study conducted in Hospital Universiti Sains Malaysia from January 2013 till March 2017. The l ist of CRE cases se lected from Medical Microbiology & Parasitology laboratory. Patient‟s records were reviewed for demographics and clinical characteristics and those that meet the inclusion and exclusion criteria were included in this study. Archived isolates were further tested for MIC testing for meropenem, imipenem, ertapenem, doripenem and polymyxin B by using E test method. The results were interpreted according to CLSI guidelines. Data were analysed using SPSS Statistic version 22. Results A total of 57 CRE infected patients and started on targeted antimicrobial therapy was included in the study. The most common infection related to CRE infection was pneumonia (29/57, 50.9%) followed by blood stream infection (15/57, 26.3%) and urinary tract infection (7/57, 12.3%) with Klebsiella pneuomoniae as a major CRE pathogen (54/57, 94.7%). Most of the patients were located in a medical ward and ICU, accounting for 42.1% (24/57) and 33.3% (19/57) respectively of the subjects. Majority of patients had underlying disease and the most common disease was chronic kidney disease (38.6%, 22/57) followed by diabetes mellitus (36.8%, 21/57). The all-30-day mortality in this study was 43.9% (42/57). Based on in vitro susceptibility testing on carbapenems, imipenem has the highest sensitivity rate (9/57, 15.8%) followed by meropenem (7/57, 12.3%) according to CLSI breakpoint 2012. All isolates were susceptible to polymyxin B. Most of the subjects in this study received monotherapy (33/57, 57.9%) compared to combined therapy (24/57, 42.1%). We found that no significant association between patient‟s outcome with monotherapy or combined therapy (p = 0.113) and also with the type of antimicrobial received. However, the 30- day mortality in combined therapy group much higher (13/23, 56.5%) if compare to monotherapy group (12/34, 35.3%). Out of 45 repeated samples cases, 82.2% (37/45) had achieved microbiological clearance. We found that no significant association between meropenem MIC levels with microbiological clearance (p = 0.641). Conclusion Overall, based on in vitro susceptibility testing polymyxin B is considered to be the most active in vitro agents against CRE. However, imipenem and meropenem still have a role in treating CRE infection especially as a combination therapy. Even though no significant association was found between antibiotic therapy with the outcome but the 30-day mortality in combined therapy group much higher than monotherapy group. This could be bias as combined therapy was started among severe infection and critically ill patients. A larger sample size and prospective study (randomised control trial) may be needed to prevent bias in term of patient‟s selection on starting type of treatment regime.